Analisis cash rasio pada koperas simpan pinjam serawai mandiri di bengkulu selatan - Saputri, Rahma; Susanti , Neri; Rahman , Abdul (Universitas Dehasen Bengkulu, 2025)
Cooperatives are an essential pillar of Indonesia's economy and play a revolutionary role in improving public welfare. The history of cooperatives in Indonesia began in 1896 with Raden Ngabei Aria Wiriatmadja in Purwokerto. This study aims to analyze the cash ratio of the Serawai Mandiri Cooperative to understand the patterns of cash inflows and outflows and to assess the cooperative's financial condition.The analysis shows that the operating cash flow ratio of 1.04 reflects the cooperative's ability to cover short-term liabilities, although the figure is close to the safe threshold. Conversely, the cash flow coverage ratio of 0.0606 indicates potential difficulty in meeting debt obligations, which could affect liquidity if not addressed promptly.The cooperative has a cash-to-interest coverage ratio of 5.23, indicating a good capacity to pay interest on its debt. Similarly, the cash coverage ratio for current liabilities of 1.04 shows a relatively stable financial position, though still vulnerable to changes in income and obligations.Investment in fixed assets is evident from the high capital expenditure ratio (14.81), reflecting a long-term strategy but one that carries risks if cash flow is insufficient. The total debt ratio of 0.232 indicates a conservative funding structure with low dependence on debt. However, the cooperative could still optimize debt financing for growth.Interestingly, the ratio of operating cash flow to net income is very high at 192.86, suggesting that operational cash flow is significantly higher than net income—an indication of high-quality earnings and sound financial health.Overall, the cooperative is in fairly good financial condition but still requires careful cash and liability management to remain stable and continue to grow.